HUBUNGAN MOVEMENT BEHAVIOUR TERHADAP TINGKAT STRES PADA REMAJA SELAMA MASA PANDEMI COVID-19 (Universitas Tarumanagara, 2022)
In December 2019 in city of Wuhan, China there were many pneumonia patients, where this pneumonia is called COVID-19 which is caused by SARS-CoV-2. Children’s health depends on adequate physical activity, lack of sedentary activity, and adequate sleep which are included in movement behaviour. However, this movement behaviour has been difficult to achieve since the COVID-19 pandemic. These three components of movement behaviour play an important role in dealing with stress. The purpose of this research to determine the relationship between movement behaviour and stress levels in adolescents at Kharisma Bangsa High School, South Tangerang by using a cross-sectional study. This research was conducted on high school student grade 1-3 with 160 students, consisting of 54 male students and 106 female students. Retrieval of data using an online questionnaire. The results showed there were most male students only met 1 movement behaviour guideline (48.1%), while most female students did not meet movement behaviour guidelines (57.5%). The level of stress on the respondents, It was found that male students who experienced low stress levels were 24.1%, those who experienced moderate stress levels were 64.8%, and those who experienced high stress levels were 11.1%, while female students who experienced low stress levels were 4.7%, those who experienced moderate stress levels were 80.2%, and those who experienced high stress levels were 15.1%. Based on the statistical test, there was no correlation between movement behaviour and stress levels with correlation coefficient (r) of -0.102 and the p value of 0.099. Keywords: Adolescents; COVID-19; Movement behaviour; Stress level AbstrakPada Desember 2019 di kota Wuhan, Cina terdapat banyak pasien pneumonia, yang kemudian disebut COVID-19 dimana SARS-CoV-2 merupakan penyebabnya. Kesehatan anak-anak tergantung pada cukupnya aktivitas fisik, kurangnya kegiatan sedentari, dan tidur yang cukup, dimana ketiga hal ini termasuk ke dalam movement behavior. Akan tetapi, movement behavior sulit tercapai semenjak pandemi COVID-19. Ketiga komponen movement behaviour ini berperan penting dalam menurunkan stres. Tujuan dari penelitian ini adalah untuk mengetahui hubungan movement behaviour terhadap tingkat stres pada remaja di Sekolah Menengah Atas Kharisma Bangsa, Tangerang Selatan menggunakan studi cross-sectional. Penelitian ini dilakukan terhadap siswa-siswi SMA kelas 1-3 sebanyak 160 responden yang terdiri dari 54 siswa dan 106 siswi. Pengambilan data menggunakan kuesioner online. Untuk menganalisis hasil data, digunakan uji pearson chi-square. Hasil penelitian yang didapatkan adalah siswa paling banyak hanya memenuhi 1 pedoman movement behaviour (48.1%), sedangkan siswi paling banyak tidak memenuhi pedoman movement behaviour (57.5%). Untuk tingkat stres pada responden, didapatkan siswa dengan tingkat stres rendah sebanyak 24.1%, dengan tingkat stres sedang sebanyak 64.8%, dan dengan tingkat stres tinggi sebanyak 11.1%, sedangkan siswi dengan tingkat stres rendah sebanyak 4.7%, dengan tingkat stres sedang sebanyak 80.2%, dan dengan tingkat stres tinggi sebanyak 15.1%. Berdasarkan uji statistik, tidak terdapat korelasi antara movement behaviour terhadap tingkat stres dengan koefisien korelasi (r) yaitu -0.102 dan nilai p yaitu 0.099.